If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = m + 19 Reorder the terms: 4 = 19 + m Solving 4 = 19 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 4 + -1m = 19 + m + -1m Combine like terms: m + -1m = 0 4 + -1m = 19 + 0 4 + -1m = 19 Add '-4' to each side of the equation. 4 + -4 + -1m = 19 + -4 Combine like terms: 4 + -4 = 0 0 + -1m = 19 + -4 -1m = 19 + -4 Combine like terms: 19 + -4 = 15 -1m = 15 Divide each side by '-1'. m = -15 Simplifying m = -15
| 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 | | -x-2/7=x+1/6+4/7 | | 12x-18=10x+10 | | 5c-4b= | | 4n+1-5n=6n+7-9n | | 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 | | (2n+2)(2n-2)= | | 14x-(10x-3)=17 | | (2/5)+=(-1/10) | | 13+(-15x)=74-12 | | (2n^2+2)(2n-2)= | | 2n+7n-28=26 | | 12x-5x=49 | | 12=3t | | 3xy+5x+2xy-8x= | | 14=2p | | 2/3(n-3)=1/3(n+6) | | 12(3x+4)-7=2x-23 |